The Challenges in Teaching English Faced By English Lecturers In South Kalimantan In Transition Situation After Covid-19 - Elsa Rosalina; Nasrullah; Inayati Fitriah Asrimawati; Rahma Pitria Ningsih (ETERNAL (English, Teaching, Learning and Research Journal), 2025)
ABSTRACT Teaching English in non-native country is kind of challenging work to do. The lecturers need to master four skills in English such as listening, speaking, reading and writing. Beside that the lecturers also must have the skill to manage the classroom and to keep the students focused on the material. The purposes of this research are to describe the challenges faced by English lecturers in South Kalimantan. This topic is chosen because the researchers are interested in finding out the experience by the lecturers when doing teaching process after 2 years they survive with Covid-19 situation, and what the challenges to teach the students who just have an online learning experiences. The qualitative method is used for this research because the findings will reveal as the information about the challenges and how they can solve it. The participants of this research are 4 lecturers from different universities in South Kalimantan that teaching English in English department and Non-English department. The researchers use interview and open ended questionnaires which have 12 questions related to the topic to collect the data. The findings of the research are as follows: first, the challenge is in technical problem like an internet connection (as the main factor which determined the successful of online and blended learning), second, dealing with the student’s motivation to participate with classroom activity because in Pandemic they are familiar with online courses. Third, about the digital literacy of the lecturers and the students related to the kind of applications that can be used for teaching and learning and how to integrated kind of application to the process itself. Last, related to classroom management and the readiness of the lecturers to face the changes in Educational sector after Pandemic.